Endoscopic calcaneoplasty with flexor hallucis longus transfer for the management of Haglund syndrome - Valya, B.; Devi, P. Savithri; Bhavya, N.; Teja, S. Dharma (International Journal of Research in Orthopaedics, 2025)
Haglund syndrome consists of a triad of posterosuperior calcaneal exostosis (Haglund deformity), retrocalcaneal bursitis, and insertional Achilles tendinopathy. Endoscopic resection of this prominence along with flexor hallucis longus (FHL) transfer is a novel technique for the treatment of Haglund syndrome. The purpose of this study is to evaluate the outcome of 10 patients presenting with Haglund disease treated by an endoscopic Haglund resection and FHL transfer. In this study, from April 2023 to August 2024, we have taken up 10 patients presenting with heel pain, diagnosed as insertional Achilles tendinopathy (IAT) with Haglund’s based on clinical findings of tenderness along Achilles tendon 2 cm proximal to the point of insertion and radiographs, with failed conservative treatment. The American Orthopaedic Foot & Ankle Society (AOFAS) ankle/hindfoot scale was used preoperatively and postoperatively to measure the functional results. A mean of 71.2 preoperative AOFAS-hind foot score which showed a significant improvement postoperatively to 3 (VAS), 82 (AOFAS) at the end of 1.5 months, 2 (VAS), 96 (AOFAS) at the end of 4 months and 1 (VAS), 97 (AOFAS) at 6 months respectively. Endoscopic calcaneoplasty with FHL transfer is a minimally invasive technique which has led to a significant improvement in preoperative and postoperative AOFAS scores and has resulted in faster recovery times with less complications.